A Comparison of the Exergy Efficiencies of Various Heat-Integrated Distillation Columns - Areej Javed; Afaq Hassan; Muhammad Babar; Umair Azhar; Asim Riaz; Rana Mujahid; Tausif Ahmad; Muhammad Mubashir; Hooi Ren Lim; Pau Loke Show; Kuan Shiong Khoo (Energies, 2022)
Distillation has relatively low thermodynamic efficiency, so it is a prime target for process intensification studies. The current research aims to study exergy losses in various heat-integrated distillation columns. A conventional industrial-scale i-butane/n-butane fractionator has been selected as a case study for the comparison of the performances of various heat-integrated designs. The Aspen Plus® process simulator is used to perform steady-state simulations and exergy analyses of the conventional distillation column (CDC), internally heat-integrated distillation column (iHIDiC), externally heat-integrated double distillation columns (EHIDDiC), and vapor recompression (VRC) systems. The results of these exergy analyses show that a modified VRC system (ηE = 10.69%) is the most efficient design for this separation. The exergy efficiency of the conventional VRC system is the same as that of the CDC (ηE = 9.27%). The EHIDDiC system (ηE = 9.77%) is somewhat better than the CDC, whereas iHIDiC shows poor exergy efficiency (ηE = 8.09%), even lower than the CDC.